Suppression of cancer-initiating cells and selection of adipose-derived stem cells cultured on biomaterials having specific nanosegments - Kao, Ta Chun; Lee, Henry Hsin Chung; Higuchi, Akon; Ling, Qing Dong; Yu, Wan Chun; Chou, Yu Hsuan; Wang, Pin Yu; Kumar, S. Suresh; Chang, Yu; Chen, Yung Hung; Chang, Yung; Chen, Da Chung; et al. (Wiley, 2014)
Cancer-initiating cells [cancer stem cells (CSCs)] in colon cancer cells can be selectively suppressed when they are cultured on Pluronic (nanosegment)-grafted dishes, whereas CSCs are maintained on conventional tissue culture dishes and extracellular matrix-coated dishes. CSCs persist in tumors as a distinct population and cause relapse and metastasis by giving rise to new tumorigenic clones. The purification or depletion (suppression) of CSCs should be useful for analyzing CSC characteristics and for clinical application. CSCs can be selectively suppressed from colon cancer cells containing adipose-derived stem cells (ADSCs) on Pluronic-grafted dishes, while ADSCs remain on the dishes. ADSCs on Pluronic-grafted dishes after the suppression of the CSCs can differentiate into osteoblasts, chondrocytes, adipocytes, cardiomyocytes, and neuronal cells. The CSCs and ADSCs exhibited different characteristics. The selection of ADSCs was possible on Pluronic-grafted dishes that suppressed the CSCs from the fat tissues of cancer patients (i.e., cell-sorting dishes), which was explained by specific biomedical characteristics of Pluronic. © 2013 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 102B: 463–476, 2014.